2009
DOI: 10.1002/jcp.21952
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism underlying muscle mass retention in hibernating bats: Role of periodic arousal

Abstract: Hibernators like bats show only marginal muscle atrophy during prolonged hibernation. The current study was designed to test the hypothesis that hibernators use periodic arousal to increase protein anabolism that compensates for the continuous muscle proteolysis during disuse. To test this hypothesis, we investigated the effects of 3-month hibernation (HB) and 7-day post-arousal torpor (TP) followed by re-arousal (RA) on signaling activities in the pectoral muscles of summer-active (SA) and dormant Murina leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 35 publications
7
52
0
Order By: Relevance
“…Such arousal bouts could help to reduce the muscle disuse stimulus for both skeletal muscle atrophy and changes in mechanical properties, in keeping with recent findings that low volume exercise can reduce muscle disuse atrophy in humans (Oates et al, 2010). Arousal from torpor bouts in bats coincides with increases in protein synthesis via activation of mammalian target of rapamycin (mTOR), helping to stop or reduce muscle atrophy during hibernation (Lee et al, 2010). The amount of muscle atrophy can dramatically differ between skeletal muscles in the same species, with different molecular pathways seemingly responsible for such differences (Nowell et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…Such arousal bouts could help to reduce the muscle disuse stimulus for both skeletal muscle atrophy and changes in mechanical properties, in keeping with recent findings that low volume exercise can reduce muscle disuse atrophy in humans (Oates et al, 2010). Arousal from torpor bouts in bats coincides with increases in protein synthesis via activation of mammalian target of rapamycin (mTOR), helping to stop or reduce muscle atrophy during hibernation (Lee et al, 2010). The amount of muscle atrophy can dramatically differ between skeletal muscles in the same species, with different molecular pathways seemingly responsible for such differences (Nowell et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…Thus, neural activation and/or neurally related trophic factors only play a small role in retaining muscle properties during hibernation. It has been suggested that shivering is a mechanism by which hibernating bats minimize the amount of muscle atrophy (Lee et al, 2010) and could be a mechanism by which disuse atrophy is minimized in hibernating bears (Harlow et al, 2004;Lohuis et al, 2007). A more likely mechanism suggested by this study is that the signaling pathways that regulate the catabolic processes of skeletal muscle are not responsive to the mechanical and neural stimuli that normally control those pathways.…”
Section: Implications For Neurally Related Pathways Regulating Musclementioning
confidence: 73%
“…The absence of any increase in calpain 1 and 2 protein abundance or their autolysed forms in aestivating C. alboguttata muscle could represent a mechanism by which aestivating frogs limit proteolysis in skeletal muscle. In agreement with our study, Lee et al (Lee et al, 2010) found no difference in the protein abundance of calpain 1 in pectoralis muscles of summer-active and 3-month hibernating Murina leucogaster bats, a species which also undergoes minimal loss in muscle mass despite inactivity during dormancy. Protein levels of both calpain 1 and 2 were also recently found to be unaffected by hibernation in squirrels (Yang et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…For example, recent studies have emphasised the importance of maintaining protein synthesis in hibernating muscle via activation of the mammalian target of rapamycin (mTOR) signalling cascade (e.g. Andres-Mateos et al, 2013;Fedorov et al, 2014;Lee et al, 2010;Nowell et al, 2011). The mTOR is a major effector of cell growth and proliferation via the regulation of protein synthesis through a multitude of downstream targets.…”
Section: Aestivating Frogs As Natural Muscle Disuse Systemsmentioning
confidence: 99%
See 1 more Smart Citation